Electrical characteristics of vapor deposited amorphous MoS2 two‐terminal structures and back gate thin film transistors with Al, Au, Cu and Ni‐Au contacts. Issue 7 (26th May 2015) - Kouvatsos, Dimitrios N.; Papadimitropoulos, George; Spiliotis, Thanassis; Vasilopoulou, Maria; Barreca, Davide; Gasparotto, Alberto; Davazoglou, Dimitris; Hoffmann, Patrik; Knez, Mato; Vahlas, Constantin; Alexandrov, Sergei
Abstract Amorphous molybdenum sulphide (a‐MoS2) thin films were deposited at near room temperature on oxidized silicon substrates and were electrically characterized with the use of two‐terminal structures and of back‐gated thin film transistors utilizing the substrate silicon as gate. Current‐voltage characteristics were extracted for various metals used as pads, showing significant current variations attributable to different metal‐sulphide interface properties and contact resistances, while the effect of a forming gas anneal was determined. With the use of heavily doped silicon substrates and aluminum backside deposition, thin film transistor (TFT) structures with the a‐MoS2 film as active layer were fabricated and characterized. Transfer characteristics showing a gate field effect, despite a leakage often present, were extracted for these devices, indicating that high mobility devices can be fabricated. SEM and EDXA measurements were also performed in an attempt to clarify issues related to material properties and fabrication procedures, so as to achieve a reliable and optimized a‐MoS2 TFT fabrication process. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)